Pemberian Antanan (Centella asiatica) dan Vitamin C Sebagai Upaya Mengatasi Efek Cekaman Panas pada Broiler - E Kusnadi; R Widjajakusuma; T Sutardi; P S Hardjosworo; A Habibie (Faculty of Animal Science, Bogor Agricultural University, 2006)
High environmental temperatures may cause heat stress in poultry. This may increase water consumption, decrease feed consumption and in turn, decrease production level. In addition, high temperature contributes to oxidative stress, a condition where oxidant activity (free radicals) exceeds antioxidant activity. In this research, antanan (Centella asiatica) and vitamin C were utilized as anti heat-stress agents for heat stressed broilers. The research used 120 male broilers of 2 - 6 weeks of age, kept at 31.98 ± 1.940C poultry house temperatures during the day and 27.36 ± 1.310C at night. The data colected were analyzed with a factorial in completely randomized design of 2 x 3 (2 levels of vitamin C, 3 levels of antanan and 4 replications) and continued with contrast-orthogonal test when necessary. The result indicated that the treatments of 5% antanan (A5), 10% antanan (A10), combination of A5C, and A10C significantly (P < 0.05) increased the plasma triiodothyronine hormone from 101 ng/dL to 113, 110, 121, 119 and 126 ng/dL respectively; carcass protein from 16.5% to 17.8%, 19.1%, 19.2%, 17.3% and 18.1%; feed consumption from 2711 g to 3026, 3071, 2883, 3156 and 2935 g and body weight gain from 1181 g to 1297, 1347, 1254, 1376 and 1330 g. It could be concluded that the combination of addition 5% antanan and vitamin C 600 ppm is the most effective as anti heat-stress agent in broilers. Key words : Centella asiatica, vitamin C, heat stress, broiler